A case study of an adverse drug reaction caused by long term use of proton pump inhibitors - Kumar, Swetha Sathish; Ravindran, Sivani; Philips, Merin Levy; B., Syaam Ganesh (International Journal of Basic & Clinical Pharmacology, 2023)
Proton pump inhibitors (PPI) are the class of drugs used to treat a wide variety of disorders related to the stomach's acid production. Although it is considered safe for short term use, reports revealed that many serious life-threatening adverse reactions occurred from long term use. Here we report a case of hypomagnesemia and hypocalcemia induced by long-term use of PPIs in a patient with crest syndrome. From his past history, it was revealed that he was on pantoprazole 40 mg for more than 3 months. While he was admitted here for other complaints, we were able to discover that he had hypomagnesemia defined by low magnesium level of 1.3 mg/dL. As a consequence, he also showed signs of hypocalcemia with a low calcium level of 7 mg/dL. A peculiar complaint seen in this patient was three episodes of supraventricular tachycardia which is the most common cardiac manifestations of hypomagnesemia. As a conclusion, hypomagnesemia can sometimes be asymptomatic and cause unspecific and serious manifestations such as asthenia, paresthesia’s, seizures, arrhythmias, and cardiac arrest. Hence routine monitoring of serum magnesium and calcium levels should be made mandatory in practice for patients on long term use of PPI. Besides, it should be kept in mind that interchanging PPI class with histamine 2 receptor antagonist or fitful use of PPI may not cause hypomagnesemia.